The Effectiveness of Using Padlet in Collaborative Writing Based on Students’ Perceptions - Ramadhani, Ayu Sinta; Dewi, Utami; Syahnaz, Mufida; Kihwele , Jimmy Ezekiel (Universitas Nahdlatul Ulama Surabaya, 2023)
The phenomena of technological growth in English instruction are expanding quickly all over the world.This progress happens not just in wealthy nations, but also in emerging nations, where the instructor mustdevelop technology-based teaching strategies and tools when teaching English. Indonesia, a developingnation, places a strong emphasis on expanding the use of technology in EFL instruction. English wassubsequently included in the general curriculum and even taught to kids in elementary schools as a directresult of this choice. This study will use Padlet as a digital tool that may be used in a writing class topique kids’ interest in learning English, especially in a writing class. Additionally, this study intends topromote the use of collaborative writing to make it simpler for elementary school pupils to use Padlets inwriting lessons. Through the use of qualitative research techniques, this study set out to learn more abouthow elementary school kids perceived using Padlets for group writing projects. A total of 52 elementaryschool kids in grades 4 and 5 participated in this study. We conducted semi-structured interviews toget data from participants. After the data has been collected, it will be processed using various contentanalysis techniques. Researchers received feedback from students who claimed that the usage of Padlets inEFL classes, particularly in collaborative writing, produced several themes. These themes include thatusing Padlet in collaborative writing can increase students’ self-confidence, that Padlet also helps studentsimprove their fluency in writing, and that Padlet is easy to use, has attractive features, and is simple tooperate.